«[E]n utmærket dagbok»: Skissens tilstedeværelse i Hamsuns tidlige prosa - Auklend, Morten (Nordlit, 2020)
This article examines how the Norwegian author Knut Hamsun deploys sketches and sketch aesthetics in his early prose from the 1890s to the early 1900s. If the sketch via Alison Byerly’s «Effortless Art: The Sketch in Nineteenth-Century Painting and Literature» can be applied as a term for determining genre, it can also be used to examine sketch-techniques, and to scrutinize an aesthetic. The sketch is also a memento for remembrance (aide-mémoire), and Hamsun’s wide array of sketch-techniques can be hallmarked not only as a modernistic impulse, but also as a way of writing complex literary prose. He assimilated several models and preliminary works in his published books, and in novels such as Hunger (1890) and Mysteries (1892) the critic can use the sketch to further recontextualise and close read Hamsun’s prose. In the travelogue In Wonderland (1903) the author directly invokes his own diaries in the published work, and the article shows how these private sketches are vital in creating a specific dialogue in the work which not only structures the story being told in the book, but highlights the importance of sketch-writing in an attempt to create both accomplished art and a metapoetic tendency that enriches the prose.